Induced G1 phase arrest of fast-dividing cells improves the quality of genomic profiles generated by array-CGH. (October 2012) - Manukjan, Georgi; Tauscher, Marcel; Ripperger, Tim; Schwarzer, Adrian; Schlegelberger, Brigitte; Steinemann, Doris
Genome-wide profiling of copy number alterations by array-based high resolution comparative genomic hybridization (array-CGH) is an important method to ensure the genomic integrity of cells in diverse conditions. We observed that the analysis of genomic profiles, in particular of fast-dividing murine leukemia cell lines, is challenging due to characteristic patterns oscillating around the array-CGH baseline. Here we show array-CGH data can be drastically improved by reducing proliferation rates of cultured cells using deprivation protocols or cell cycle inhibitors. Arresting cell cycle in the G1 phase leads to smoother genomic profiles, and hence to a more reliable detection of copy number alterations.